The Effect Of Work Discipline and Work Environment On Employee Loyalty Of The Post Office Operations Division Main Branch Surabaya 60000 - Algi Ardiyansyah; Endang Iryanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The goal of this study is to determine how employee loyalty is affected by work environment and discipline in the operations division of the Surabaya Main Branch Post Office 60000. Primary data from questionnaires given to respondents served as the basis for this study. Structural Equation Model-Partial Least Square (SEM-PLS) is a statistical analysis tool used in research data processing that use partial least squares analysis methodologies. According to the study’s findings, employee loyalty is positively impacted by work environment and discipline.